Low‐intensity vibration increases cartilage thickness in obese mice. Issue 2 (5th December 2017) - Pamon, Tee; Bhandal, Vincent; Adler, Benjamin J.; Ete Chan, M.; Rubin, Clinton T.
ABSTRACT: Obesity is associated with an elevated risk of osteoarthritis (OA). We examined here whether high fat diet administered in young mice, compromised the attainment of articular cartilage thickness. Further, we sought to determine if low‐intensity vibration (LIV) could protect the retention of articular cartilage in a mouse model of diet‐induced obesity. Five‐week‐old, male, C57BL/6 mice were separated into three groups ( n = 10): Regular diet (RD), High fat diet (HF), and HF + LIV (HFv; 90 Hz, 0.2g, 30 min/d, 5 d/w) administered for 6 weeks. Additionally, an extended HF diet study was run for 6 months (LIV at 15 m/d). Articular cartilage and subchondral bone morphology, and sulfated GAG content were quantified using contrast agent enhanced μCT and histology. Gene expression within femoral condyles was quantified using real‐time polymerase chain reaction. Contrary to our hypothesis, HF cartilage thickness was not statistically different from RD. However, LIV increased cartilage thickness compared to HF, and the elevated thickness was maintained when diet and LIV were extended into adulthood. RT‐PCR analysis showed a reduction of aggrecan expression with high fat diet, while application of LIV reduced the expression of degradative MMP‐13. Further, long‐term HF diet resulted in subchondral bone thickening, compared to RD, providing early evidence of OA pathology—LIV suppressed the thickening, such that levels were not significantly different from RD. These data suggest that dynamic loading, via LIV, protected the retention of cartilage thickness, potentially resulting in joint surfaces better suited to endure the risks of elevated loading that parallel obesity. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:751–759, 2018. Abstract : Obesity is associated with increased osteoarthritis risk. We examined whether high fat diet compromised the attainment of articular cartilage thickness, and if low‐intensity vibration (LIV) could protect the retention of cartilage in an obese mouse model. Contrary to our hypothesis, HF cartilage thickness was not different from RD. However, LIV increased cartilage thickness, which was maintained when diet and LIV were extended into adulthood. LIV, may result in joint surfaces better suited to endure the risks of obesity.